Client participation in medical rehabilitation for adults with severe disabilities - Aila Järvikoski; Jouni Puumalainen; Kristiina Härkäpää (Scandinavian Journal of Disability Research, 2013)
The Social Insurance Institution (SII) of Finland arranges medical rehabilitation for people with severe disabilities. The rehabilitation process requires collaboration between the client and several organizations and professionals. The study aimed to find out what kind of experiences persons with disabilities had on their possibilities of participation in the planning and process of rehabilitation, and what factors were associated with the degree of their participation in the rehabilitation process. The study group was chosen using stratified sampling from among rehabilitation clients. The data were gathered using a questionnaire survey. Over half of the clients reported having participated actively in the rehabilitation planning and most found that their opinions had been taken into account at least fairly well during the planning phase. The results indicate that special attention should be paid to developing client-driven approaches in the rehabilitation system and to supporting the participation of clients who have difficulties in expressing their needs because of their illness, disability, or educational and social backgrounds.